Electrical and Optical Improvement of Gambier Dye Modification to Enhance DSSC Performance - Mohd Azizan, N.; D.G. Saputri; Ahmad, M.K.; Ramli, K.N.; Ahmad, M.Y. (International Journal of Integrated Engineering, 2026)
DSSCs, or dye-sensitized solar cells, are a more affordable alternative than silicon-based photovoltaics. This study aims to optimize important parts to increase DSSC efficiency. The photoanode material is titanium dioxide (TiO2) nanoparticles, which are utilized because of their large surface area and effective electron transport. Advanced fabrication and surface treatments enhance the stability and light-harvesting performance of TiO2 films. New natural and metal-organic dyes' absorption, attachment strength, and charge transfer features are created and analyzed. The relationship between dyes and the TiO2 surface is modified to increase electron injection efficiency. The electrolyte composition is improved to improve ionic conductivity and reduce recombination losses. Power conversion efficiency (PCE), short-circuit current density (Jsc), open-circuit voltage (Voc), and fill factor (FF) are among the performance parameters that are examined. Based on the experimental data, the fabricated DSSC using the pure ruthenium dye possessed the highest level of power conversion efficiency (PCE) is 1.25%, fill factor (FF) is 45.97%, short-circuit current density (Jsc) is 3.98 mA/cm2 and open-circuit voltage (Voc) is 0.85 V.  The modified dyes performed better than the pure gambier dye, which only obtained a PCE of 0.43% with a PCE of 1.09%, Jsc: 3.56 mA/cm2, Voc: 0.74 V, FF: 51.13%. The combination of two dyes enhanced the dye loading and electron transfer due to the fact that the agglomeration was less and nanoparticle coverage became homogenous as evident by the FESEM images.  The increased UV-Vis and IPCE absorption spectra of the combination dye in the 400 to 700 nm range were also evidenced by the UV-Vis and IPCE data. These findings indicate that, even though such natural dyes as gambier can save money and save the environment without causing significant changes in performance, synthetics such as ruthenium are more efficient.  Significant potential strategies toward environmentally benign, rather efficient DSSCs with large-scale industrial potential are evidenced by the successful combination of natural and synthetic sensitizers.